Equivalent noise level response to number of vehicles: a comparison between a high traffic flow and low traffic flow highway in Malaysia - Halim, Herni; Abdullah, Ramdzani (Springer, 2013)
In this study, 5 days measurement of noise level during peak hour and off peak hour has been carried out at two types of highways; high traffic flow highway (Sungai Besi Expressway) and low traffic flow highway (Duke Highway). Findings indicated that heavy traffic flow highway recorded higher noise level compared to low traffic flow highway. It was due to the higher number of vehicles on the heavy traffic flow highway than low traffic flow highway. At certain i.e. above 500, noise level is stabilized.